2000
DOI: 10.1161/01.atv.20.3.689
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Uptake of Radiolabeled MDA2, an Oxidation-Specific Monoclonal Antibody, Provides an Accurate Measure of Atherosclerotic Lesions Rich in Oxidized LDL and Is Highly Sensitive to Their Regression

Abstract: Abstract-To determine whether labeled antibodies against oxidized LDL (OxLDL) offer advantages for quantifying atherosclerosis, we compared in vivo aortic uptake of 125 I-labeled MDA2, a monoclonal antibody against malondialdehyde-lysine epitopes), atherosclerotic surface area, and aortic weight in Watanabe heritable hyperlipidemic and New Zealand White rabbits and in low density lipoprotein receptor-deficient (LDLR Ϫ/Ϫ ) and apolipoprotein E-deficient (apoE Ϫ/Ϫ ) mice. Absolute and specific uptakes of 125 I-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
87
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 113 publications
(94 citation statements)
references
References 54 publications
6
87
1
Order By: Relevance
“…One possibility is that both OxPL and Lp(a) are derived from disrupted plaque contents, inasmuch as both have been previously documented to be enriched in atherosclerotic lesions in vivo. [1][2][3]5,9,10,20 In fact, recent work in animal models demonstrates that OxLDL can be imaged noninvasively with radiolabeled oxidation-specific antibodies. 2,5 Sev- …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that both OxPL and Lp(a) are derived from disrupted plaque contents, inasmuch as both have been previously documented to be enriched in atherosclerotic lesions in vivo. [1][2][3]5,9,10,20 In fact, recent work in animal models demonstrates that OxLDL can be imaged noninvasively with radiolabeled oxidation-specific antibodies. 2,5 Sev- …”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] In animals, OxLDL within plaques is preferentially depleted in response to regression/antioxidant diets. [5][6][7] In humans, plaque specimens from carotid and coronary arteries are significantly enriched in OxLDL 1,3 and become depleted in OxLDL after treatment with statins. 8 In particular, unstable plaques appear to be preferentially enriched in OxLDL, 9,10 and OxLDL in plasma has been shown to be associated with acute coronary syndromes 9,11,12 and endothelial dysfunction.…”
mentioning
confidence: 99%
“…It has been shown that lesion regression is associated with decreased levels of oxidation epitopes present in LDL within the lesion. 46 A reduced level of oxidized lipids within the arterial wall may result in plaque regression by reducing macrophage accumulation. Aggressive lipid lowering did not affect several other features of the advanced plaque, such as calcification and the presence of cholesterol clefts.…”
Section: Discussionmentioning
confidence: 99%
“…LDL lowering decreased oxLDL content within apoB-100 -immunoreactive areas and likely limited the enhanced lipid peroxidation that occurs in hypercholesterolemia. 25 Tsimikas et al 26 demonstrated that dietary lipid lowering in hypercholesterolemic mice decreased in vivo uptake of the antibody for oxLDL (MDA2) to a greater degree than other features of atherosclerosis. These changes should mitigate EC dysfunction and inflammatory cell infiltration in atherosclerotic arteries.…”
Section: Discussionmentioning
confidence: 99%